Total Actuarial Liabilities and Normal Costs Using The Unit Credit Method - Gusliana, Shindi Adha (Indonesian Operations Research Association (IORA), 2021)
The pension fund program requires an actuarial calculation, such as the amount of actuarial obligations and normal costs for each pension fund participant. Total actuarial liabilities are calculated to show the company's liability for pension benefits for pension fund participants. Funding in pension funds is obtained from the normal costs or contributions paid by participants to the pension fund. By using the unit credit method, the total value of actuarial liabilities at 1/1/2020 is IDR 405,338.5. Then by using the unit credit method, it is projected that the normal cost on 1/1/2019 is IDR 1,071.43. The calculation method on funding aims to ensure that the collected pension plan funds will be sufficient to pay pension benefits to participants when they retire.